2015
DOI: 10.1007/s10973-015-5145-4
|View full text |Cite
|
Sign up to set email alerts
|

Thermodynamic study of competitive inhibitors’ binding to urease

Abstract: Three competitive inhibitors of urease: boric acid, 2-mercaptoethanol and phosphate buffer pH 6.45, were subjected to the studies of temperature effects on their binding to the enzyme. The first of their kind for these systems, the studies were carried out at temperatures between 15 and 35°C in HEPES buffers. The Michaelis K M and inhibition K i constants determined for the uninhibited and inhibited urease reactions, respectively, were found to increase with an increase in temperature, importantly, the inhibit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
17
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 19 publications
(17 citation statements)
references
References 67 publications
(113 reference statements)
0
17
0
Order By: Relevance
“…The reaction was carried out in 22 mM phosphate buffer solution of pH 7 at 25 °C in a constant shaker water bath. The concentration of the buffer solution was selected such that it had a negligible competitive inhibitory action on URE . In the case of free URE, reaction was initiated by the addition of 0.5 mL URE (1 mg/mL) into 4.5 mL of 50 mM urea.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…The reaction was carried out in 22 mM phosphate buffer solution of pH 7 at 25 °C in a constant shaker water bath. The concentration of the buffer solution was selected such that it had a negligible competitive inhibitory action on URE . In the case of free URE, reaction was initiated by the addition of 0.5 mL URE (1 mg/mL) into 4.5 mL of 50 mM urea.…”
Section: Methodsmentioning
confidence: 99%
“…The concentration of the buffer solution was selected such that it had a negligible competitive inhibitory action on URE. 28 In the case of free URE, reaction was initiated by the addition of 0.5 mL URE (1 mg/mL) into 4.5 mL of 50 mM urea. The amount of ammonia produced during 15 min of reaction was determined followed by addition of 2.5 mL acetic acid solution (10 v %) to stop the reaction.…”
Section: Membrane Characterizationsmentioning
confidence: 99%
“…Its elucidation is crucial for the efficacious use of the enzyme and for the control of its activity. One way to achieve this control is by using inhibitors [5] , [25] , [26] , [27] , [28] , the primary among them being: amides and esters of phosphoric acid [22] , [29] , [30] , thiols [30] , [31] , [32] , hydroxamic acids [29] , [30] , [33] , [34] , phosphinic and thiophosphinic acids [35] , boric acid [29] , [32] , [36] , phosphate [30] , [32] , [37] , [38] , heavy metal ions [39] , [40] , bismuth compounds [41] , quinones [42] , [43] , [44] , and fluoride [29] , [45] .…”
Section: Ureasementioning
confidence: 99%
“…45 It is claimed that -SH groups blockade was achieved through a nucleophilic addition into the carbonyl bond at C1 of usnic acid (Figure 1), a condition that can be reversed in the presence of Cys or dithiothreitol. 46 The mechanism of partial inactivation and reactivation of urease by (S)-(-)-UA (2) seems to be similar to that of omeprazole. 44b Indeed, the kinetics and interaction profiles for (S)-(-)-UA (2) revealed that this lichen metabolite is a typical mixed inhibitor.…”
Section: Lichen Compound T ( O C)mentioning
confidence: 89%
“…Finally, (R)-(+)-UA (1) interacts preferably with urease active site by electrostatic forces as demonstrated by kinetics/interaction assays in a manner compared with other already reported for known urease inhibitors (Figure 7). 46 and its interaction with hydroxyurea (b), 47 omeprazole after reaction with Cys residue (c) 44a or (R)-(+)-UA (1) (d; proposed model). W1-W3, water molecules in the active site; WB, bridging water (hydroxide form).…”
Section: Lichen Compound T ( O C)mentioning
confidence: 99%